Modelling the impact of respiratory syncytial virus (RSV) vaccine and immunoprophylaxis strategies in New Zealand. Issue 31 (13th July 2021) - Prasad, Namrata; Read, Jonathan M.; Jewell, Christopher; Waite, Ben; Trenholme, Adrian A.; Huang, Q. Sue; Grant, Cameron C.; Newbern, E. Claire; Hogan, Alexandra B.
Highlights: Mathematical models of respiratory syncytial virus (RSV) transmission can help describe seasonal epidemics and assess the impact of potential vaccines and immunoprophylaxis with monoclonal antibodies (mAb). Our models suggest that either a maternal RSV vaccine or mAb would effectively reduce RSV hospitalization disease burden in New Zealand. A seasonal mAb resulted in a larger RSV disease prevention impact than a maternal vaccine. Abstract: Background: Mathematical models of respiratory syncytial virus (RSV) transmission can help describe seasonal epidemics and assess the impact of potential vaccines and immunoprophylaxis with monoclonal antibodies (mAb). Methods: We developed a deterministic, compartmental model for RSV transmission, which was fitted to population-based RSV hospital surveillance data from Auckland, New Zealand. The model simulated the introduction of either a maternal vaccine or a seasonal mAb among infants aged less than 6 months and estimated the reduction in RSV hospitalizations for a range of effectiveness and coverage values. Results: The model accurately reproduced the annual seasonality of RSV epidemics in Auckland. We found that a maternal vaccine with effectiveness of 30–40% in the first 90 days and 15–20% for the next 90 days could reduce RSV hospitalizations by 18–24% in children younger than 3 months, by 11–14% in children aged 3–5 months, and by 2–3% in children aged 6–23 months. A seasonal infant mAb with 40–60% effectiveness for 150 days could reduce RSV hospitalizations by 30–43%, 34–48% and by 14–21% in children aged 0–2 months, 3–5 months and 6–23 months, respectively. Conclusions: Our results suggest that either a maternal RSV vaccine or mAb would effectively reduce RSV hospitalization disease burden in New Zealand. Overall, a seasonal mAb resulted in a larger disease prevention impact than a maternal vaccine.